THE INFLUENCE OF CORPORATE GOVERNANCE, OWNERSHIP STRUCTURE ON COMPANY VALUE WITH COMPANY SIZE AS MODERATION VARIABEL ( - Rahim, Ilham; Mediaty, Mediaty; Damayanti, R. A. Damayanti (Universitas Patria Artha, 2018)
The research aimed at investigating the influence of the corporate governance (size of board ofdirectors, proportion of independent of board of commissioners as proxy), ownership structure(managerial ownership, foreign ownership as proxy) on the company value, and finding out theinfluence of the company size moderation in relation to the corporate governance, ownershipstructure on the company value. The research population was all manufacturing companies registered in Indonesia StockExchange (ISE) as many as 143 companies. Samples were taken using the purposive samplingtechnique by the criteria determined. The samples obtained were as many as 96 companiesduring the observation period of 3 years. The data were analyzed using the multiple linearregression analysis and Moderated Regression Analysis (MRA). The research result indicates that the size of board of directors has the significant andpositive influence on the company value, the proportion of independent board of commissionersdoes not have the significant effect on the company value, the managerial ownership does nothave the significant impact on the company value, the foreign ownership has the significant andpositive influence on the company value. The research indicates the empirical evidence that thecompany size moderates the corporate governance on the company value, whereas the companysize can not moderate the ownership structure on the company value.